PENGARUH PENERAPAN BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. AGRIMITRA UTAMA PERSADA PEKANBARU - Khaisar Nugraha; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Purchasing Decision is one of the fundamental factors in the application of the marketing concept, and with the development of the industrial world and increasingly competitive industrial competition, especially in implementing the right strategy in an effort to improve consumer purchasing decisions, it becomes a phenomenon that forms the basis or background of this research. The right marketing mix and good service quality are supporting instruments and even important instruments that indicate a company is able to attract market interest. The Marketing Mix Strategy and Service Quality is the implementation of the SMS as Air Minum Dalam Kemasan (AMDK) produced by PT. Agrimitra Utama Persada Pekanbaru. This study has a purpose to determine the Marketing Mix, Service Quality and Purchase Decisions at PT. Agrimitra Utama Persada Pekanbaru. The method used in this research is descriptive and quantitative, with primary data sources and secondary data. The analytical method used in this research is a series of statistical tests in the form of; simple and multiple linear regression analysis, and by going through the validity and reliability tests. In this study the results obtained are the Marketing Mix (X1) has a positive and significant effect on purchasing decisions (Y), and Service Quality (X2) has a positive and significant effect on Purchase Decisions (Y) At PT. Agrimitra Utama Persada Pekanbaru.Keywords: Maeketing Mix, Service Quality and Purchase Decision